Therapeutic management of fibrosis in systemic sclerosis patients – an analysis from the Swiss EUSTAR cohort - Kevin Windirsch; Suzana Jordan; Mike Oliver Becker; Cosimo Bruni; Rucsandra Dobrota; Muriel Elhai; Ion-Alexandru Garaiman; Carmen-Marina Mihai; Michele Iudici; Paul Hasler; Camillo Ribi; Britta Maurer; et al. (Swiss Medical Weekly, 2024)
OBJECTIVES: Systemic sclerosis is a chronic autoimmune connective tissue disease leading to microvascular and fibrotic manifestations in multiple organs. Several treatment options and recommendations from different European countries are available. In this study, for which the ambit is Switzerland specifically, we aim to describe the treatment patterns of systemic sclerosis patients with fibrotic manifestations.